Fear of Missing Out dan Narsisme: Faktor Pendorong Adiksi Instagram di Kalangan Mahasiswa - Kholisah, Nur; Suhesty, Aulia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The advancement of internet technology and social media, particularly Instagram, has significantly impacted students' lives, with Fear of Missing Out (FoMO) and narcissism suspected as driving factors behind Instagram addiction. This research seeks to assess the impact of fear of missing out and narcissism on Instagram addiction among university students using a quantitative approach with multiple linear regression analysis. This research included 75 students from the Faculty of Cultural Sciences at Mulawarman University, recruited by purposive sampling. The used data gathering techniques included the instagram addiction scale, fear of missing out scale, and narcissism scale. The used data analysis method was multiple linear regression. The findings indicate that FoMO and narcissism significantly influence Instagram addiction, contributing 79.1% to the variance, with FoMO having a beta coefficient (β) of 0.372 and narcissism 0.555. Thus, FoMO and narcissism are significant factors driving Instagram addiction among students, negatively affecting their academic and social lives.